TINGKAT PARTISIPASI ANGGOTA PADA KOPERASI UNIT DESA (KUD) KUSUMA BAKTI DESA SIALANG KUBANG KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR - Liberson Sinaga; Eri Sayamar; Cepriadi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to; (1) to analyze the level of participation of members of the Koperasi Unit Desa (KUD) Kusuma Bakti; (2) Knowing the obstacles encountered in increasing the participation of members of the board. Research conducted at Koperasi Unit Desa (KUD) Kusuma Bakti the Village Sialang Kubang Subdistrict Perhentian Raja Kampar Regency. The study conducted by using method of survey, the method of sampling was done by Simple Random Sampling, and the samples taken 33 people of the total population. The collecting data of this research was using primay data and secondary data. To analyzed the degree and the problem at participation of this research was using descriptive method. To obtain the degree of participation of members in contributing or mobilize its resources, member participation in decision making, and participation of members in enjoying benefits. Data were analyzed with the participation level Likert’s Summated Rating Scale. The study concluded that the overall level of participation of members of KUD Kusuma Bakti get a total score of 2.25 (1.67 to 2.33 are included in the category of medium participation rates). In another side, the programs KUD Kusuma Bakti had some problem that related by the degree of participant were passive in cooperative activities, attendance gave ideas on meeting, and participant in activity and evaluation of programs village cooperatives Kusuma Bakti.     Keywords : Participation, KUD Kusuma Bakti, Scale Likert’s